(untitled) (Web of Teachers: Inderscience Research, 2025)
The importance and methods of use of pedagogical approaches are analyzed in the process of effective training of handball sports. Innovative methods and methods will be considered to teach young people in the technical and tactical bases of sports. Teach us what pedagogical techniques should be used in teaching the soups. For example, the application of group work and roleplaying games can be effective for young people. For students, these methods teach not only to play a game, but also to solve problems.